Adjuvant therapy in pancreatic cancer - Jones, Owain Peris (Baishideng Publishing Group Inc, 2014)
Pancreatic cancer remains one of the leading causes of cancer related death worldwide with an overall five-year survival of less than 5%. Potentially curative surgery, which alone can improve 5-year survival to 10%, is an option for only 10%-20% of patients at presentation owing to local invasion of the tumour or metastatic disease. Adjuvant chemotherapy has been shown to improve 5-year survival to 20%-25% but conflicting evidence remains with regards to chemoradiation. In this article we review the current evidence available from published randomised trials and discuss ongoing phase III trials in relation to adjuvant therapy in pancreatic cancer.